Impact of Lean Management Practices on Operational Performance: An Empirical Investigation from Construction Supply Chain of Pakistan - Shahbaz, Muhammad Saeed; Shaikh, Fazal Ali (International Journal of Sustainable Construction Engineering and Technology, 2020)
Construction sector is considered as the backbone for any country, whereas, supply chain has become an essential part of all industries. Thus, the construction supply chain emerged as a new, independent and crucial segment. During the last few decades, this industry has affected greatly in Pakistan due to unfavorable conditions like inflation, political unrest and the war against terrorism. However, various strategy and approaches are available in the literature that helps this industry to tackle the problems by creating efficiency and effectiveness. Lean management is considered a decisive element for every organization; by applying lean approaches, organizations can enhance the performance for not only the manufacturing sector but also service sectors. The aim of this study is to explore the potential benefits of lean approaches (Total Quality Management, Using 5’s Services and Quick Change Over) in the construction supply chain of Pakistan. Questionnaire has been distributed to the construction supply chain of Pakistan by systematic probability sampling. The population of this study consists of listed construction companies in the ‘Pakistan Engineering Council’. Meanwhile, after the screening, 367 responses have been considered and valid for data analysis. The Pearson correlation result indicates that there is strong correlation between Total Quality Management and Operational Performance with r = 0.801. The study performed multiple regressions analysis and found that has a positive impact on the Operational Performance, Using 5S Practices and Quick Change Over. The results revealed that all three approaches positively and significantly enhance. This study will help the organizations to better understand how construction managers can reduce their workload; make their operations more efficient and productive.